Brain Activation in Response to Low-Calorie Food Pictures: An Explorative Analysis of a Randomized Trial With Dapagliflozin and Exenatide - van Ruiten, Charlotte C.; Veltman, Dick J.; Nieuwdorp, Max; IJzerman, Richard G. (Frontiers in Endocrinology, 2022)
Background and aim: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) induce less weight loss than expected. This may be explained by SGLT2i-induced alterations in central reward- and satiety circuits, contributing to increased appetite and food intake. This hyperphagia may be specific for high-calorie foods. Glucagon-like peptide-1 receptor agonists (GLP-1RA) are associated with lower preferences for high-calorie foods, and with decreased activation in areas regulating satiety and reward in response to high-calorie food pictures, which may reflect this lower preference for energy dense foods. To optimize treatment, we need a better understanding of how intake is controlled, and how ((un)healthy) food choices are made. The aim of the study was to investigate the effects of dapagliflozin, exenatide and their combination on brain activation in response to low-calorie food pictures. Methods: We performed an exploratory analysis of a larger, 16 week, double-blind, randomized, placebo-controlled trial. Sixty-eight subjects with obesity and type 2 diabetes were randomized to dapagliflozin, exenatide, dapagliflozin plus exenatide, or double placebo. Using functional MRI, the effects of treatments on brain responses to low-calorie food pictures were assessed after 10 days and 16 weeks. Results: Dapagliflozin versus placebo decreased activity in response to low-calorie food pictures, in the caudate nucleus, insula, and amygdala after 10 days, and in the insula after 16 weeks. Exenatide versus placebo increased activation in putamen in response to low-calorie food pictures after 10 days, but not after 16 weeks. Dapagliflozin plus exenatide versus placebo had no effect on brain responses, but after 10 days dapagliflozin plus exenatide versus dapagliflozin, increased activity in insula and amygdala in response to low-calorie food pictures. Conclusion: Dapagliflozin decreased activation in response to low-calorie food pictures, which may reflect a specific decreased preference for low-calorie foods, in combination with the previously found increased activation in response to high-calorie foods, which may reflect a specific preference for high-calorie foods, may hamper SGLT2i-induced weight loss. Exenatide treatment increased activation in response to low-calorie foods. Combination treatment may lead to more favorable brain responses to low calorie food cues, as we observed that the dapagliflozin-induced decreased response to low-calorie food pictures had disappeared.